An investigation of hydrogen-fuelled HCCI engine performance and operation - Gomes Antunes, J.M.; Mikalsen, R.; Roskilly, A.P. (International journal of hydrogen energy, 2008)
This paper presents the findings of an experimental investigation into the operation of a compression ignition (CI) engine in homogeneous charge compression ignition (HCCI) mode using hydrogen fuel. Factors that were investigated include engine efficiency, emissions and mechanical loads. Hydrogen was found to be a possible fuel for operation of a CI engine in HCCI mode. The heat release rate is extremely high, which leads to high ignition timing control requirements. The ignition timing was controlled using heating of the inlet air, and satisfactory performance was demonstrated using this method. Some cycle-to-cycle variations were, however, observed due to the difficulty in achieving accurate control of ignition timing. Use of hydrogen in HCCI engines allows operation with very lean air–fuel mixtures, giving extremely low emissions of nitrogen oxides and other pollutants. Operation with an excess air ratio of 6 was demonstrated, and a maximum fuel efficiency of 45% was achieved with an excess air ratio of 3. The maximum power of the engine in HCCI mode is, however, quite modest, being limited by the need for inlet air heating to ensure autoignition, which reduces the air mass flow through the engine. There are also mechanical limitations to the operation of the HCCI hydrogen engine at high loads due to higher rates of pressure rise and in-cylinder peak pressures compared to conventional diesel mode.